A retained foreign body granuloma mimicking a left ventricular psuedoanuerysm - Patrini, Davide (Int J Surg Case Rep, 2016)
INTRODUCTION: Gossypiboma, also referred to as a textiloma, gauzoma or muslinoma describe a mass in the body composed of a central cotton core surrounded by a foreign body reaction. It has an estimated incidence of 1/1000–1/10000 surgeries, occurring in the abdomen (56%), pelvis (18%) and least commonly the thorax (11%) and represents an unfortunate event for both the patient and the operating surgeon with severe liability implications. PRESENTATION OF CASE: We report a case of a 49-year-old male with Marfan Syndrome who was admitted to the cardiology department with a four day history of shortness of breath and associated dull, non-radiating chest pain. Past history included a previous Bentall procedure for a type-A aortic dissection and coronary artery bypass grafting involving a saphenous vein graft to the right coronary artery. A computed tomography (CT) scan showed a round, heterogeneous mass measuring 14 × 9 cm with lobulated contours, situated adjacent to the left ventricle along the left posterior region of the aorta. The mass was resected and further dissection revealed a plastic band harboured from the core of the mass. DISCUSSION: The majority of cases of intrathoracic gossypiboma present as intractable cough or an incidental finding on radiological evaluation. Dyspnoea alone is relatively underreported as a presenting symptom of this condition CONCLUSION: This case highlights the important clinical history features for diagnosing this surgical error, including persistent respiratory symptoms and a history of cardio-thoracic surgery. It also emphasizes on the need for implementing definite strategies to prevent the occurrence of gossypiboma in surgical practice.